ISU PEMERATAAN DAN KEADILAN AKSES PENDIDIKAN DASAR (STUDI KASUS SDN 151 INPRES KALAMPA KABUPATEN TAKALAR) - Riswanto; Suardi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The main problem in basic education is the inequality and injustice of access to education, which includes geographical, economic, and facility factors. This study aims to identify contemporary issues related to the equity of basic education at SDN 151 Inpres Kalampa, Takalar Regency. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and document analysis. The results show that although accessibility is physically adequate, there are still gaps in digital facilities and the quality of human resources. Data from the school shows student literacy levels are still in the medium category and several students face distance barriers. This study recommends a more inclusive policy through digital infrastructure optimization and local government support for low-income families.